Making Boundaries and Site Plans in Nambo Village, Lasalimu District, Buton Regency - sayfullah, Muh; Idwan, Idwan; Efendi, Ahmad; Agusman, Agusman; Aldha, Sitti Febriyany (Lembaga Riset dan Inovasi Masyarakat Madani, 2022)
Buton Regency is a Level II region in the Indonesian province of Southeast Sulawesi. Nambo Village is comprised of three hamlets: Nambo, Lagonturu, and Tandaompure. It has an area of 25.5 kilometers. When it comes to carrying out operations, both government and community social, the people of Nambo community constantly promote mutual collaboration. The Village Government and Karangtaruna both have programs for planning and designing village boundaries and site plans, however relevant parties lack the skills or knowledge to participate in the planning and design process. The debate outcomes resulted in the design of the Nambo village border and site layout, as well as the materials to be utilized in the village boundary construction process. To enhance the look of the border, mountain stone foundations, brick walls, and natural stone are employed